2007
DOI: 10.2202/1556-3758.1088
|View full text |Cite
|
Sign up to set email alerts
|

Cassava Mash Dewatering Parameters

Abstract: A study was conducted to evaluate the parameters affecting the dewatering of cassava mash during processing. First, studies on the pressure distribution within the mash during the dewatering were carried out. Experimental equipment consisting of tyre tube filled with water, a copper tube, and a pressure gauge was designed and fabricated to measure pressure used in expressing the juice contained in the grated cassava mash. It also included a cylindrical dewatering tank made of galvanized steel plate and a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…Although mechanical peelers have been developed and tested, their use is still not widespread (Ohimain, 2014), mostly because of high proportion of wastages. Hence, hand peeling is currently the only feasible option (Kolawole et al, 2012). Equipment such as mechanical graters, hydraulics jacks, motorized sieves and flash dryers have been adopted to speed up HQCF production and to improve the quality (Sanni et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mechanical peelers have been developed and tested, their use is still not widespread (Ohimain, 2014), mostly because of high proportion of wastages. Hence, hand peeling is currently the only feasible option (Kolawole et al, 2012). Equipment such as mechanical graters, hydraulics jacks, motorized sieves and flash dryers have been adopted to speed up HQCF production and to improve the quality (Sanni et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Time for dewatering is very critical and it should be as little as possible. Kolawole et al (2012) reported that improved dewatering system with a mechanical press can successfully dewater grated cassava mash with 2 -4 hours. Cassava flour produced under rapid dewatering systems precluding fermentation mostly produce flour with low pH, which is one of the challenges faced by small processors.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is done after the frying operation. The texture and consistency of processed cassava food products is an important consideration throughout sub-saharan Africa [25].…”
Section: Sievingmentioning
confidence: 99%
“…Apart from the peelers, various types of cassava-grating machines have also been developed [11,12]. Other unit operations involved in cassava processing include dewatering of cassava pulp (mash), drying and frying, which are still majorly carried out manually [13,14]. There are several factors nevertheless, to be considered before the usage and implication of technical devices for these unit operations.…”
Section: Cassava Processingmentioning
confidence: 99%